2009
DOI: 10.1111/j.1478-3231.2008.01866.x
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profile of Huh‐7 cells expressing hepatitis C virus genotype 1b or 3a core proteins

Abstract: The expression of HCV core proteins of different genotypes leads to a specific gene expression profile. This may account for the variable disease expression associated with HCV infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 45 publications
1
14
0
1
Order By: Relevance
“…We have chosen 48 h as the time point for study because the maximum expression level of HCV core protein after transfection was reached (Fig. 1a), consistent with our previous findings (Abid et al, 2005;Pazienza et al, 2007Pazienza et al, , 2009). …”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…We have chosen 48 h as the time point for study because the maximum expression level of HCV core protein after transfection was reached (Fig. 1a), consistent with our previous findings (Abid et al, 2005;Pazienza et al, 2007Pazienza et al, , 2009). …”
Section: Introductionsupporting
confidence: 66%
“…It has been shown that growing cells in delipidated medium reduce the triglyceride accumulation induced by HCV core protein genotype 3a, suggesting a lack of de novo synthesis of triglycerides (Abid et al, 2005) and suggesting that the core protein seems to promote a mere redistribution of fat-laden vesicles typically found in Huh-7 cells, rather than a true triglyceride accumulation. On the other hand, the core protein alone is able to modulate the expression of several cellular genes involved in lipid metabolism (Pazienza et al, 2009) and/or to promote de novo triglyceride synthesis (Lerat et al, 2009). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCV replication and viral protein expression lead to differential expression of host genes as determined by microarray or proteomic studies (1)(2)(3). A breakthrough in HCV research was the discovery of an HCV strain, JFH1, capable of replicating efficiently and of producing viral particles in cultured cells (4)(5)(6).…”
mentioning
confidence: 99%
“…Using microarray analysis Pazienza et al [15] compared the gene expression profile of Huh7 cells transfected with the core protein of HCV genotype 1b and 3a, leading to the conclusion that several genes involving lipid transport and metabolism were up-or down-regulated in a genotypespecific manner. This fact could explain the variable disease expression associated with HCV infection.…”
Section: Pathogenesis Of Steatosis In Hepatitis Cmentioning
confidence: 99%